Technology for early childhood education and socialization [ developmental applications and methodologies - Blake, Sally , 1949-; Izumi-Taylor, Satomi , 1948- (Information Science Reference, 2010)
"This book provides readers with valuable and authentic research on how technology relates to early childhood growth"--Provided by publisher.